2 '- 1-(2-hydroxyphenyl)ethylidene benzene-sulfonohydrazide - Ali, Hapipah Mohd; Ng, S.W.; Jefrey, B.W.; Laila, M. (International Union of Crystallography, 2007)
The molecules of the title compound, C14H14N2O3S are, linked by an N-H center dot center dot center dot O-sulfonyl hydrogen bond into a chain.